Experimental Investigations of Self-adjusting Bionic Flaps on Low-aspect Ratio Wings - A. Verma; V. Kulkarni; S. Shinde (Journal of Applied Fluid Mechanics)
Self-adjusting flexible flap is a biomimetic passive flow control device, which is evolved by emulating the covert feathers on the upper wing of a bird. The effectiveness of such a flap was explored mostly for infinite or high aspect ratio (AR) wings from low to high Reynolds numbers (Re) in prior studies. However, the aerodynamic characteristics of a high AR wing are completely different from the lower one due to wingtip vortices. Therefore, in the present work, this flap is tested on a S5010 profiled wing of two different low ARs, 2.0 and 1.0, in the Re range of MAVs application. Three flap chord lengths (0.12c, 0.15c, and 0.20c) are examined at various chord-wise positions (0.3c to 0.8c). Results show that the optimal performance enhancement is achieved when flaps cover 80% of the wingspan for AR 2.0 and 70% for AR 1.0. The flap does not impact pre-stall wing performance, but it significantly improves post-stall lift and drag characteristics over the clean wing. Increasing the flap chord from 0.12c to 0.15c increases wing performance, but increases beyond 0.15c provide no additional beneficial effects. The optimal chord-wise position of the flap for better performance enhancement is near the mid-chord for both models. Multiple flap configurations have a relatively lower lift-enhancing capability than single flap configurations. The effect of Re on the flap effectiveness decreases with decreasing AR of the wing.